Safety, Tolerability and Treatment Outcomes Between a Generic Fixed-Dose Combination (GPO-VIR S30) and Standard Triple Regimen of Stavudine/Lamivudine/Nevirapine in HIV-Infected Children - สุนทรขจิต, รุจนี; วรเดชวิญญู, สิมากานต์; สุวรรณมาศ, ดวงมณี; บุญฤทธิภัทร์, นฤภัค; อุทยมกุล, สุมนมาลย์ (Disease Control Journal, 2007)
This study aimed to compare safety, tolerability and treatment outcomes between HIV-infected children who received fixed-dose combination of stavudine (d4T), lamivudine (3TC) and nevirapine (NVP) named GPO-VIR S30 with the standard separated triple regimen of d4T/3TC/NVP. Fifty naïve HIVinfected children aged under 15 years were randomized into 2 groups, 25 children in each group. The study group received GPO-VIR S30 that cut into the fraction of ¼, ½, ¾, and entire tablet. The dosage was calculated based upon NVP dose of 120-200 mg/m2. The control group received d4T 1 mg/kg, 3TC 4 mg/kg and NVP 160-200 mg/m2. The results showed that one (4%) child in GPO-VIR S30 group and two (8%) in d4T/3TC/NVP group needed to change NVP due to severe skin rash (P = 0.552). The percentage of skin rash grade 1-2 was 15.8% in GPO-VIR S30 group and 9.5% in d4T/3TC/NVP group (P = 0.550). Two and one children in the study group and control group respectively (P = 0.552) died. Immune reconstitution syndrome (IRS) was diagnosed in one case in study group and 4 cases in control group (P = 0.157). Nineteen (76%) children in study group and 21 (84%) in the control group continued antiretroviral therapy through 12 months (P = 0.480). The children receiving d4T/3TC/NVP had significantly higher rate of nausea/vomiting than GPO-VIR S30 group (P = 0.045). The immunologic outcomes (CD4) at 6 and 12 months were not different between the two groups (P = 0.503, P = 0.851). By OT analysis at 12 months of treatment, 73.7% of study group and 38.1% of control group had HIV-1 RNA <50 copies/mL, P = 0.024. However by ITT, there was no significant in this outcome, 56% versus 32%, P = 0.087. This study indicated that divided GPO-VIR S30 tablet for HIV-infected children was safe, well tolerate and effective as standard separated triple regimen of d4T/3TC/NVP.